Phagocytosis-Inflammation Crosstalk in Sepsis: New Avenues for Therapeutic Intervention - Hortová-Kohoutková, Marcela; Tidu, Federico; De Zuani, Marco; Šrámek, Vladimír; Helán, Martin; Frič, Jan (Shock, 2020)
Phagocytosis is a complex process by which cells within most organ systems remove pathogens and cell debris. Phagocytosis is usually followed by inflammatory pathway activation, which promotes pathogen elimination and inhibits pathogen growth. Delayed pathogen elimination is the first step in sepsis development and a key factor in sepsis resolution. Phagocytosis thus has an important role during sepsis and likely contributes to all of its clinical stages. However, only a few studies have specifically explored and characterized phagocytic activity during sepsis. Here, we describe the phagocytic processes that occur as part of the immune response preceding sepsis onset and identify the elements of phagocytosis that might constitute a predictive marker of sepsis outcomes. First, we detail the key features of phagocytosis, including the main receptors and signaling hallmarks associated with different phagocytic processes. We then discuss how the initial events of phagosome formation and cytoskeletal remodeling might be associated with known sepsis features, such as a cytokine-driven hyperinflammatory response and immunosuppression. Finally, we highlight the unresolved mechanisms of sepsis development and progression and the need for cross-disciplinary approaches to link the clinical complexity of the disease with basic cellular and molecular mechanisms.
Keywords: sepse; Sepsis; fagocytóza; cytokiny; signální transdukce; Phagocytosis; Cytokines; Animals; lidé; Immunosuppression Therapy; imunosupresivní léčba; Humans; zvířata; Signal Transduction